Culture Based Stunting Education through Madihin and Traditional Taboos as Pillars of Family Parenting - Annisa Febriana; Yulia Yunara; Nur Hikmah; Rizky Ridha Anshari; Hidayah Putri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting remains a major public health problem in Indonesia, including Banjar Regency, South Kalimantan. Effective prevention requires an educational approach that is not only evidence-based but also culturally sensitive to ensure community acceptance. Integrating local wisdom, such as the oral art of madihin and traditional taboos, is considered effective because it aligns with the socio-cultural values of the Banjar community. This study aimed to evaluate the effectiveness of stunting education based on Banjar culture through madihin videos (traditional oral art), live madihin performances, and the reinforcement of traditional taboos as pillars of healthy family parenting. A quasi-experimental design with a pre-test–post-test control group was employed. The sample consisted of 100 families with toddlers in Banjar Regency, divided into 50 intervention and 50 control participants. Sampling technique used was purposive sampling. The intervention provided education on stunting, exclusive breastfeeding, complementary feeding, traditional taboos, and parenting through videos and live madihin performances, which included health messages and discussions on Banjarese traditional taboos related to diet, pregnancy, and childcare. Data were analyzed using Wilcoxon test to compare pre-test and post-test scores within groups, and Independent t-test to compare differences between intervention and control groups. The intervention group showed a significant improvement in knowledge and attitudes. The mean knowledge score increased from 26.94 to 31.58 (p=0.001), while the attitude score rose from 38.68 to 47.78 (p=0.001). In contrast, the control group showed only a small increase in knowledge (24.80 to 25.20; p=0.001) and no significant change in attitude (20.21 to 29.79; p=0.108). These findings indicate that a culture-based approach is more effective in improving knowledge and fostering positive family attitudes than conventional education. Health education that incorporates madihin and traditional taboos can serve as a strategic innovation in health promotion, particularly in stunting prevention through strengthening family parenting practices in Banjar Regency.